Prevalence and Correlates of HIV and Hepatitis B Virus Coinfection in Northern Alberta. Issue 1 (2014) - Pittman, Carmen; Plitt, Sabrina; Birse, Ted; Doucette, Karen; Romanowski, Barbara; Cooper, Rya; Houston, Stan; Shafran, Stephen; Singh, Ameeta E
Abstract : BACKGROUND: HIV and hepatitis B virus (HBV) share transmission routes, and coinfection is associated with higher morbidity and mortality. To date, no Canadian studies have examined HIV-HBV coinfection. OBJECTIVES:To examine the prevalence and correlates of HIV and HBV coinfections in Northern Alberta. METHODS: The present study was a retrospective database review of all HIV-infected (HIV+) individuals in Northern Alberta from 1982 to 2010 and a chart review of HBV surface antigen-positive individuals for whom charts were available (46.2%). RESULTS: Of 2844 HIV+ patients, 2579 (90.7%) had been tested for HBV surface antigen, and 143 (5.5%) of these were HBV coinfected. Coinfected males were primarily Caucasian (70.8%), and coinfected females were primarily black (56.4%) or Aboriginal (31.3%). Coinfected individuals were more likely to be male (88.1% versus 71.3%; P<0.001) and to have died (34.3% versus 17.9%; P<0.001). CONCLUSIONS: The prevalence of coinfection with HBV in HIV-infected patients in Northern Alberta is lower than reported in other developed nations. The pattern of coinfections in Northern Alberta likely follows immigration trends. Recognition and management may be improving with time; however, further research and additional strategies are required to enhance the prevention, identification and management of HBV infection in HIV-infected individuals.